2020
DOI: 10.1104/pp.19.00760
|View full text |Cite
|
Sign up to set email alerts
|

Putative cis-Regulatory Elements Predict Iron Deficiency Responses in Arabidopsis Roots

Abstract: Plant iron deficiency (2Fe) activates a complex regulatory network that coordinates root Fe uptake and distribution to sink tissues. In Arabidopsis (Arabidopsis thaliana), FER-LIKE FE DEFICIENCY-INDUCED TRANSCRIPTION FACTOR (FIT), a basic helix-loophelix (bHLH) transcription factor (TF), regulates root Fe acquisition genes. Many other 2Fe-induced genes are FIT independent, and instead regulated by other bHLH TFs and by yet unknown TFs. The cis-regulatory code, that is, the cis-regulatory elements (CREs) and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 128 publications
(215 reference statements)
0
20
0
Order By: Relevance
“…Moreover, bZIP transcription factors are predicted trans‐acting factors that regulate Fe deficiency responses, based on a computational approach for enrichment of putative cis‐regulatory elements in the promoters of Fe deficiency response genes (Schwarz et al . 2020). Because of these strong associations of FIT with CIPK11 and ABI5, we consider it reasonable to postulate that FIT is linked with ABI5.…”
Section: Common Players In Aba Drought/salt Stress and Fe Deficiency Signallingmentioning
confidence: 99%
“…Moreover, bZIP transcription factors are predicted trans‐acting factors that regulate Fe deficiency responses, based on a computational approach for enrichment of putative cis‐regulatory elements in the promoters of Fe deficiency response genes (Schwarz et al . 2020). Because of these strong associations of FIT with CIPK11 and ABI5, we consider it reasonable to postulate that FIT is linked with ABI5.…”
Section: Common Players In Aba Drought/salt Stress and Fe Deficiency Signallingmentioning
confidence: 99%
“…Separate studies showed that systematic analysis of transcriptome datasets is powerful in the identification of the cistrome behind a complex reaction [7,8,19]. The basic assumption in these studies, as well as in the metaRE algorithm, is that only robust and significant cis-element association with transcriptional response will be detected across multiple, diverse transcriptomic datasets that test similar experimental variables.…”
Section: Metare Tool For Identification Of Cis-regulatory Elements Rementioning
confidence: 99%
“…They revealed enrichment of transcription factors binding sites in the DEGs and their association with external factors that cause similar changes in the organism. An interesting approach has been applied to study the cistrome for iron deficiency response in Arabidopsis (Arabidopsis thaliana) roots [8]. Authors searched for the enrichment of k-mers in upstream regulatory regions of Fe-responsive genes taken from several experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning approaches have provided new and powerful ways for understanding and predicting gene expression in plants (Azodi et al, 2020b; Wang et al, 2020b; Washburn et al, 2019). These approaches have been used to predict expression levels (Washburn et al, 2019; Sartor et al, 2019), regulatory architecture (Mejía-Guerra and Buckler, 2019), as well as gene expression responses to abiotic stress (Zou et al, 2011; Uygun et al, 2017, 2019; Azodi et al, 2020a; Schwarz et al, 2020). These studies highlight the potential to develop predictive models that use putative cis-regulatory motifs to predict gene expression responses to stress.…”
Section: Introductionmentioning
confidence: 99%